If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 6y = 11 + -4x Solving 3 + 6y = 11 + -4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6y = 11 + -3 + -4x Combine like terms: 3 + -3 = 0 0 + 6y = 11 + -3 + -4x 6y = 11 + -3 + -4x Combine like terms: 11 + -3 = 8 6y = 8 + -4x Divide each side by '6'. y = 1.333333333 + -0.6666666667x Simplifying y = 1.333333333 + -0.6666666667x
| 4x-3+3x=11 | | -2(2x-6)=4x | | -0.7x=14 | | 30+.25n=20+.32n | | x+5*2x=17 | | 13x-22=2(9x+10) | | 4(-2m+7)=-28 | | -(-16)-x=13 | | 2(a-2)=a+5 | | 2.2x-5=2.8x+6 | | 3(s-10)=24 | | 8x^2+56=0 | | 15-11x=108 | | 45n^2+10=0 | | 45n^2+10=0 | | 9m+10(-14m)=-5 | | .5(3x-2)=5 | | 8+2x-16+x=-15 | | 95=5x^2 | | 2z-3-8z+1= | | x^2+3xy+2y^2-x+2y+2=0 | | -4x-10-1x=25 | | 2x^2-20=0 | | 5X+2=Y | | 14s^2-21s=0 | | 2x-6+8=14 | | 5[1-8x]=5-8x | | .125(w-7)=5 | | 12x^2+5x-7=0 | | 0.222222222x-0.333333333=1 | | .25(d-5)=1 | | 18y-2x=26 |